Self Medication Practices of Reproductive Age Group Women in Thiruvananthapuram District, South India: A Questionnaire – Based Study - M.G. Sangeetha Nair; T.P. Rajmohanan and J. Kumaran
Objective: To assess the prevalence of self medication practice among the women of reproductive age group and the identification of various socio- demographic variables influencing self medication practice. Study Design: A community-based cross-sectional descriptive study was conducted from September 2008 to March 2009 among the women in the age group of 15 to 49 years in the Sreekariyam, situated in Thiruvananthapuram District, Kerala, South India. Simple random sampling was done to choose the study population. Methods: By using a semi-structured questionnaire, the study was carried out on 250 respondents residing rural and urban area of Sreekariyam. Socio- demographic data, information regarding the type of medication, illness for which the medication was used and what are the sources of health information was collected by direct interview method and analysed by using statistical package for the social sciences (SPSS) software. Results: Majority of respondents, (59.2%) were aged between 35-49 years, 54% were residing in urban area, 68% were married, 42% were housewives, 29.6% were studied up to high school level and 37.2% belonged to low income category. 138 respondents were engaged in self medication. Health magazines and health workers were the important sources of health information. Head ache, dyspnoea and leg pain were the common health problems. Analgesics and antipyretics were commonly used. Old prescription was the most important source of self medication. Conclusion: Though the study population was educated and having good awareness with excellent health care facilities, the self medication practice was found to be prevalent in the study area. The results of the study emphasize the need for comprehensive measures including information, training, legislation and education at all levels to rationalize the drug therapy. A similar study with larger sample size and pharmacy based epidemiological studies are necessary for further investigations in the future.